2007
DOI: 10.1016/j.neures.2007.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Diminished degradation of myelin basic protein by anti-sulfatide antibody and interferon-γ in myelin from glia maturation factor-deficient mice

Abstract: In this study we show the effect of anti-sulfatide (RmAb) antibodies and inflammatory cytokines, TNF-α and IFN-γ in inducing myelin basic protein (MBP) degradation in myelin isolated from control wild type (WT) and glia maturation factor (GMF)-deficient (GMF-KO) mice. GMF was not detected in isolated myelin from WT and GMF-KO mice although it is present in brains of WT mice. Our results show that calcium dependent neutral protease activity caused significantly elevated degradation of 18.5 and/or 17.5 kDa isofo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
(50 reference statements)
1
3
0
Order By: Relevance
“…We reported that the overexpression of GMF in astrocytes leads to the destruction of primary oligodendrocytes, the myelin-forming cells in the central nervous system, by interactions between astrocytes, microglia, and oligodendrocytes. These results suggested a novel pathway of GMF initiated cytotoxicity of brain cells, and implicated its involvement in the pathogenesis of inflammatory demyelinating diseases of the central nervous system such as multiple sclerosis/ experimental autoimmune encephalomyelitis (Menon et al, 2007;Zaheer et al, 2007a;Zaheer et al, 2007b;Zaheer et al, 2007c;Zaheer et al, 2007d). In the present report we show that the overexpression of GMF in neuroblastoma N18 cells directly induces caspase-dependent apoptosis mediated by GSK-3β activation.…”
Section: Introductionsupporting
confidence: 65%
“…We reported that the overexpression of GMF in astrocytes leads to the destruction of primary oligodendrocytes, the myelin-forming cells in the central nervous system, by interactions between astrocytes, microglia, and oligodendrocytes. These results suggested a novel pathway of GMF initiated cytotoxicity of brain cells, and implicated its involvement in the pathogenesis of inflammatory demyelinating diseases of the central nervous system such as multiple sclerosis/ experimental autoimmune encephalomyelitis (Menon et al, 2007;Zaheer et al, 2007a;Zaheer et al, 2007b;Zaheer et al, 2007c;Zaheer et al, 2007d). In the present report we show that the overexpression of GMF in neuroblastoma N18 cells directly induces caspase-dependent apoptosis mediated by GSK-3β activation.…”
Section: Introductionsupporting
confidence: 65%
“…The BN-77 Reo-2 strain, isolated from bovine diarrheal matter, was grown on HmLu-1 cells as described previously (33). One-day-old mice were i.p.…”
Section: Virus Isolationmentioning
confidence: 99%
“…This mixture was used for assay of IL-4, IFN-γ, and GAPDH mRNAs. The primers used for these genes (Table 1) [ [23][24][25] were made based on mouse sequences to amplify the fragments spanning exon/intron junction.…”
Section: Real-time Rt-pcr Analysismentioning
confidence: 99%